Self-Esteem and Self-Efficacy's Impact on Employee Performance - Marwah Marwah; Muhammad Kasran (LP3M Universitas Putra Bangsa, 2022)
Employee performance determines a company's success. Employee performance is influenced by two factors: self-esteem and self-efficacy. The purpose of this study was to see if self-esteem and self-efficacy, either separately or together, had any effect on employee performance. This study employs a quantitative research design. With a sample size of 150, the population in this study was employees of PT. Sumber Graha Sejahtera (SGS). The data analysis method uses multiple linear regressions. Data was collected through primary data sources, especially direct questionnaire distribution to respondents. Results and findings Self-esteem and self-efficacy were found to have a positive and significant impact on employee performance. The role of self-efficacy and self-esteem in improving employee performance: research implications Improve self-efficacy so that employees are confident in their ability to complete tasks. Employee confidence is increased by providing development efforts for individual employees, such as improving formal employee education, providing training, providing supervision in the execution of employee duties, and (ii) increasing self-esteem so that employee confidence increases. Efforts that can be made by delegating full responsibility and authority to employees based on their position, as well as providing opportunities for employees to gain self-development for their work, such as by promoting employees to different levels of positions, assigning assignments based on their competencies, and so on.